2018
DOI: 10.11114/jets.v6i2.2643
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation between Multiple Intelligences and Learning Styles

Abstract: Exploring learning style and multiple intelligence type of learners can enable the students to identify their strengths and weaknesses and learn from them. It is also very important for teachers to understand their learners' learning styles and multiple intelligences since they can carefully identify their goals and design activities that can teach to the different intelligences, and design student-centered activities. This study aims to reveal secondary school students' multiple intelligences and learning sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 7 publications
3
42
0
2
Order By: Relevance
“…In the case of student, determining learning styles can be highly beneficial and useful. [ 11 ] In addition, the learner can enjoy decisions that may improve the outcomes of learning process and increase the student's satisfaction with the education process. [ 7 9 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…In the case of student, determining learning styles can be highly beneficial and useful. [ 11 ] In addition, the learner can enjoy decisions that may improve the outcomes of learning process and increase the student's satisfaction with the education process. [ 7 9 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…The importance of environmental issues also encourages research that examines the profile of REB and NI, although it is still rarely found. Some of the research studying students' REB profile (Ntanos, Kyriakopoulos, Arabatzis, Palios, & Chalikias, 2018;Pan et al, 2018) and some researchs are studying students' NI profile (Raskanda, Suwarma, & Liliawati, 2018;Şener & Çokçalışkan, 2018). Unfortunately, studies that examine student personality profiles are difficult to find.…”
Section: Introductionmentioning
confidence: 99%
“…The instrument for IQ was 15 items of multiple choices are used. Furthermore, the instrument was valid to test because it was taken from Saputra's book (Saputra, 2015) in Seberapa Cerdaskah Anda? Berapa Nilai IQ Anda?…”
Section: Methodsmentioning
confidence: 99%